Effect of frame design on the fracture strength of a zirconia crown and porcelainfaced crown - Kuroda S.; Shinya A.; Gomi H. (Japanese Society for Dental Materials and Devices, 2022)
In this study, we investigated the effect of frame design on the fracture strength of a zirconia crown and porcelain-faced crown, with the aim of clinically applying a zirconia crown fabricated using computer-aided design and manufacturing. The results showed that the fracture strengths were 645.9 MPa with Frame Design 1, 759.5 MPa with Frame Design 2, and 989.7 MPa with Frame Design 3, suggesting that the fracture strength improved depending upon the frame design. The above information suggests that it is necessary for the zirconia crown frame form to have an occlusal surface table where the crown design has a reduced outer diameter, instead of using the conventional form of covering the abutment tooth with a thickness of 0.5 mm. © 2019, Japanese Society for Dental Materials and Devices. All rights reserved.